PENGARUH KEGIATAN MONTASE TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI TK KEMALA BHAYANGKARI I PEKANBARU - Ade Riska Muthiakanza; Zulkifli N Zulkifli N; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study was to determine how much influence the montage activity had on the fine motoric abilities of children aged 5-6 years at TK Kemala Bhayangkari I Pekanbaru, which numbered 15 children. In the research that was made into the population were children of TK Kemala Bhayangkari I Pekanbaru aged 5-6 years consisting of 2 classes. Based on the results of observations there is 1 class that has a low interest in children's learning. So that the population in this study were 15 children from TK Kemala Bhayangkari I Pekanbaru. The sample is partly / representative of the population studied. The sample of the study was a class B child consisting of 15 children at TK Kemala Bhayangkari I Pekanbaru. The data analysis technique used is an experiment that uses data from one group pretest posttest design, then the formula used is a t-test using the SPSS 16 program. The data collection tools in this study use the observation sheet. Based on the results of the study, the results of t count = 23,367 are greater than t table = 2,145. Thus Ho = rejected and Ha = accepted. It means that in this study there were influences of Montage Activities before and after on fine motor skills at TK Kemala Bhayangkari I Pekanbaru. In simple terms, this research has succeeded in improving children's fine motor skills. Although in this study the level of influence of montage activities on the fine motor skills of children at Kemala Bhayangkari I Kindergarten in Pekanbaru was low, namely 29.45%, this was due to the lack of motivation of children to learn in montage activities besides the lack of concentration of children in montage activities. children do montage activities some children play and even disturb other friends because the time used for montage activities is quite long, making children bored and eventually play and lack concentration.Key Words: Fine Motoric Ability, Montage Activities.